PENENTUAN PERSEDIAAN BAHAN BAKU KOPRA PADA PT. SALIM IVOMAS PRATAMA Tbk DENGAN PENDEKATAN EPQ (ECONOMIC PRODUCTION QUANTITY) - Anthon J.E. Madilah; Agung Sutrisno; Jefferson Mende (JURNAL POROS TEKNIK MESIN UNSRAT, 2013)
One of the factor to minimize the total cost is increasing the efficiency staples of copra, to avoid raw materials shortage that will make the production process stopped or the company will paying more for storage when the raw materials is excessive. This research is applying EPQ (Economic Production Quantity) method to determine the quantity and the period of staples ordering in a palm oil industries, using PT. Salim Ivomas Pratama Tbk as a case study. By using EPQ method, the company could anticipating the gradually arrival of raw materials. Financially, EPQ method is more optimal in ordering the raw materials. The calculation resulted, the value of Q0 (order quantity) is 79.539,90 tons and T0 (order period) is 1,29 months. Applying EPQ will profit the company. Keyword : EPQ, Order quantity, Order period